L’adaptation du contexte institutionnel : condition sine qua non du développement durable des palmeraies camerounaises - Oriane Plédran; Sylvain Rafflegeau; Patrice Levang (VertigO)
The palm oil sector has proven competitive and profitable. Environmentally friendly farming techniques exist and there is room for improving the production of smallholder plantations. A sustainable development of the palm oil sector is possible but the business models have to be reconsidered through the setting up of micro or mini palm oil mills in degraded or deforested areas, and fostering the development of smallholder plantations in contract with agro-industries. Therefore, an adapted framework has to be put in place as a prerequisite for a sustainable development trajectory of the palm oil sector - e.g. enhancing production methods that are economically viable (higher yields per hectare, disease and pest control, etc.), socially equitable (respect for workers' rights, consent of local communities, etc.) and protecting the environment (biodiversity conservation, climate change mitigation and adaptation, etc.). Such improvement should operate at two levels : by developing synergies between smallholders and agro-industries and by facilitating the access to land to local and vulnerable communities at the local level ; by capacity building and by strengthened political and economic governance at national level, in order to enforce the existing laws and encourage sustainability among the different stakeholders involved in the sector.